Figurative Language Found in “Wolf Town” Movie - Paulina Merlin; Ida Ayu Putri Gita Ardiantari (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
Abstract This study entitled “figurative language found in “Wolf Town” movie. The purposes of this study are to identify the types of figurative language and to analyze the meaning of figurative language used in Wolf Town movie. This study used two theories. The first theory used in this research is proposed by Stanford (2003) and keraf (2009) which is used to find out types of figurative language used in Wolf Town movie. The second theory is proposed by keraf (2009) Which is used to find out the meaning of figurative language used in Wolf Town movie. The method used in collecting the data was observation method. The data of the movie were collected by downloading movie from the youtobe, watching the movie, listening and understanding the dialogue movie and taking note and classifying the data based on type’s figurative language. The data were analysed descriptively by using qualitative method. After analyzing the data, it was found that there are seven types of figurative language used in Wolf Town movie which consist of 1 simile (9%), 2 hyperbole (18%), 1 symbolism (9%), 1 sarcasm (9%), 4 repetition (37%), 1 cynicism (9%), and 1 allegory (9%). All of the figurative language have connotative meaning which implicitly deliver hidden messages and life values. Keywords: figurative language, movie, figurative language meaning. Abstrak Penelitian ini berjudul “figurative language found in “Wolf Town” movie”. Tujuan dari penelitian ini adalah untuk mengidentifikasi jenis-jenis bahasa khiasan dan menganalisis makna bahasa khiasan di movie Wolf Town. Penelitian in menggunakan dua teori. Teori pertama dikemukakan oleh Stanford (2003) dan Keraf (2009) yang digunakan untuk mengetahui jenis-jenis Bahasa khiasan yang digunakan dalam movie Wolf Town. Teori kedua dikemukakan oleh Keraf (2009) yang digunakan untuk mengetahui makna makna bahasa khiasan yang digunakan dalam movie Wolf Town. Metode yang digunakan dalam pengumpulan data adalah metode observasi. Penulis mengumpulkan data skrip movie dengan mendownload movie dari youtobe, nonton movie, mendengarkan dan memahami dialog movie dan mencatat dan mengklasifikasi data, berdasarkan jenis bahasa khiasan. Penulis menganalisis data secara deskriptif dengan menggunakan metode kualitatif. Setelah menganalisis data, penulis menemukan bahwa ada tujuh jenis bahasa khiasan yang di temukan di movie Wolf Town yang terdiri dari 1 simile (9%), 2 hiperbola (18%), 1 simbolik (9%), 1 sarkasme (9%), 4 repetisi (37%), 1 sinisme (9%), dan 1 alegory (9%). Semua bahasa khiasan memiliki makna konotatif yang secara implisit menyampaikan pesan-pesan tersembunyi dan nilai-nilai kehidupan.